THE VALUES OF DHIKRULLAH AS A STIMULUS FOR CHARACTER STRENGTHENING - Iskandar Iskandar (Jurnal Ikhtibar Nusantara, 2025)
Character as an accumulation of the interaction of values ​​with the human psyche has been the object of psychological studies by scientists to this day. The debate questions the relevant values ​​in self-development to strengthen character. Although there has been a cognitive revolution, no study has been found that involves the values ​​of dhikrullah as a character stimulus. The vibration of dhikrullah contains values ​​that can function to develop self-awareness to strengthen character. This study is an academic response to the need for values ​​as a stimulus in strengthening character. The author collected qualitative data to find the relevant values ​​of dhikrullah as a stimulus to strengthen character. The results of the study show that the values ​​of dhikrullah can be a stimulus that strengthens character. The values ​​of dhikrullah can be a stimulus variable to increase self-awareness. The effect of dhikrullah affects emotions such as feelings of emotion, crying and joy. Therefore, the author concludes that continued awareness of the values ​​contained in zikullah can strengthen your character. The results of this study are useful in building character through the dhikrullah values ​​approach.